TEACHER PERFORMANCE IMPROVEMENT PROGRAM UNDER SUPERVISOR ACADEMIC SUPERVISION - Andiono, Nurkilat (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to describe the implementation of teacher performance improvement programs under the academic supervision of supervisors at MI Foster Paiton District. To find out the implementation of academic supervision carried out by school supervisors regarding teacher performance, to find out the model of academic supervision at MI Foster Paiton District, and to find out the increase in teacher performance as the impact of academic supervision at MI Foster Paiton District.